Analysis of Information Search Behaviour Based on The Age of Indonesian Outbound Traveler - Batari Toja, Tenri Muthia; K. Kausar, Devi Roza; Puspita, Nungky; Yuan, Yulan (Prasetiya Mulya Publishing, 2021)
This study aims to determine trends in choosing information channels and conducting overseas travel activities with a focus on